General anesthetics and cytotoxicity: possible implications for brain health - Armstrong, Ryden; Xu, Fenglian; Arora, Anish; Rasic, Nivez; Syed, Naweed I. (Drug and chemical toxicology (New York, N.Y. 1978), 2017)
Background: The search for agents that bring about faster induction and quicker recovery in the operating room have yielded numerous anesthetics whose mechanisms of action and potential toxic side effects remain unknown, especially in the young and aging brain. Objective: Taking advantage of our clinical and basic science expertise, here we subject the reader to an interesting perspective vis-à-vis the current applications of general anesthetics, and present evidence for their neurotoxic effects on the developing and elderly brains. Results: Recent studies have called into question the safety of general anesthetics, especially with regards to potentially significant detrimental impacts on the developing brains of young children, and cognitive decline in the elderly - often following multiple episodes of anesthesia. Despite accumulating evidence from animal studies demonstrating that general anesthesia leads to neurodegeneration and cognitive impairment, to date a clear consensus on the impact of anesthetics in humans remains elusive. Because a direct impact of anesthetics on human neuronal networks is often difficult to deduce experimentally, most laboratories have resorted to animal models - albeit with limited success in translating these findings back to the clinic. Moreover, the precise mechanisms that lead to potential cognitive, learning, and memory decline in young and elderly patients also remain to be fully defined. Conclusions: This review will focus primarily on the cytotoxic effects of anesthetics, and offer some practical resolutions that may attenuate their long-term harm. An urgent need for studies on animal models and an increased focus on highly controlled prospective epidemiological studies is also reinforced.